PENGARUH TINGKAT PERHATIAN ORANG TUA DAN PERAN SERTA GURU AGAMA ISLAM TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK KELAS VII DI SMP NEGERI 54 SURABAYA - Miftakhul Djannah; Ufi Juroidah; Dian Triana; Atim S (FAI- Undar, 2021)
Parents have a major role towards the formation of character. Attention, responsibility and trust of parents felt by children will be the basis of imitation, and kontifikasi themselves to behave. This means that parents need to introduce and give a sense of moral values to children as the foundation and direction of behaving. Then a teacher of Islam also has immense task in forming the character, that whole build skills and good attitudes of students in accordance with the teachings of Islam.This study aims to determine how much the level of attention of parents and the role of the teacher Islam to the character formation of students in SMP Negeri 54 Surabaya.This research method using quantitative and qualitative research design. The use of these two methods is expected to benefit close to one another weakness. This research is specially selected for this study conducted an intensive, detailed and fundamental about an object where researchers take the case of parental attention and participation of teachers Islam to the character formation of students in SMP Negeri 54 Surabaya.Population and samples were taken using the technique of